2020
DOI: 10.1177/1354068820968839
|View full text |Cite
|
Sign up to set email alerts
|

Radical right parties and anti-feminist speech on Instagram: Vox and the 2019 Spanish general election

Abstract: Radical right-wing parties often use the attack on feminism as a central argument in their political discourse. The Spanish political party Vox, born in 2013, is a good example of this phenomenon. This paper analyzes Vox’s Instagram posts for the party’s two last electoral campaigns previous to the two successive general elections held in Spain in 2019. After the collection, selection and quantification of these data, we carried out a qualitative analysis of the semantic networks created through the utilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 49 publications
1
18
0
6
Order By: Relevance
“…The analysis of the hashtag #Sus-tainableTourism has corroborated this hypothesis, although it has shown that the accounts with the most influence and activity are those of official entities, well above individual or personal accounts. According to the commented authors, Twitter is the social network most chosen by official entities, governments, political parties or politicians in office [46,47,48,49,50,51,52]. The research data confirm that the most active accounts in sustainable tourism are of this nature and maintain the validity and timeliness of these previous research [23,24,25].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The analysis of the hashtag #Sus-tainableTourism has corroborated this hypothesis, although it has shown that the accounts with the most influence and activity are those of official entities, well above individual or personal accounts. According to the commented authors, Twitter is the social network most chosen by official entities, governments, political parties or politicians in office [46,47,48,49,50,51,52]. The research data confirm that the most active accounts in sustainable tourism are of this nature and maintain the validity and timeliness of these previous research [23,24,25].…”
Section: Discussionsupporting
confidence: 67%
“…The chosen social media has been Twitter because it allows you to view tweets without having to be registered as a user. Likewise, Twitter is considered the social network where governments, politicians and institutions are most present [46,47,48,49,50,51,52,53,54]. Considering the reports of the introduction and underlining that the ecological commitment must come from governments, institutions and companies [55,56,57,58,59], the social media for microblogging was chosen as the most adequate to meet the objectives of the study.…”
Section: Methodsmentioning
confidence: 99%
“…The party champions traditional, highly conservative values. It is resolutely antifeminist, putting centre-stage its opposition to "gender ideology" and the dismantling of what it refers to as feminist, LGBTQ, and other leftist "lobbies" (Bernardez-Rodal et al, 2020;Olivas Osuna & Rama, 2021). In this way, it shares traits with Poland's Law and Justice Party.…”
Section: Vox: a Brief Historymentioning
confidence: 99%
“…The first study concludes that VOX's posts aim to recruit activists: "The discourse is that of a civil resistance movement" (Aladro Vico & Requeijo Rey, 2020, p. 221). According to Bernardez-Rodal et al (2020, p. 3), VOX's social media strategy was designed, in part, by Trump associate Steve Bannon, who appeals to basic emotions and seeks to construct a "closed group identity built around the feeling of loss of traditional values. "…”
Section: Social Media and Party Buildingmentioning
confidence: 99%
“…This reflects authoritarianism since certain roles are considered to be pre-determined and every attempt at modifying them entails a reaction. In the discourse of VOX this is particularly evident about gender roles and anti-feminist rhetoric (Bernardez-Rodal et al, 2020). This results in a patent hostility towards feminism as an ideology with the proposal of suppressing "subsidized radical feminist organization (VOX Manifesto: 17).…”
Section: Vox As a Populist Radical Right Partymentioning
confidence: 99%